Propionibacterium acnes as a possible pathogen of granuloma in patients with ocular sarcoidosis. Issue 11 (7th March 2017) - Goto, Hiroshi; Usui, Yoshihiko; Umazume, Akihiko; Uchida, Keisuke; Eishi, Yoshinobu
Abstract : Background/aims: To detect Propionibacterium acnes from intraocular granuloma in patients with ocular sarcoidosis. Methods: Ten patients (10 eyes) with uveitis associated with sarcoidosis, who underwent vitrectomy to remove the epiretinal membrane were analysed. The patients were 70.4±7.6 (mean±SD) years of age, and the observation period from diagnosis of sarcoidosis until vitrectomy was 27.6±15.1 months. Histopathological examination of paraffin-embedded sections of the excised epiretinal membranes was conducted by H&E staining and immunohistochemical staining using PAB antibody, which is a monoclonal antibody against P. acnes . Four patients with idiopathic epiretinal membrane and four patients with epiretinal membrane caused by chronic uveitis other than sarcoidosis were included as control. Results: Granuloma in the epiretinal membrane was observed in 4 of 10 patients with sarcoidosis, and all the granulomas were positive for PAB. In one patient without granuloma in the epiretinal membrane, PAB immunoreactivity was found in inflammatory cells, presumably macrophages. No granuloma and no PAB immunoreactivity were detected in all control patients, except one with chronic uveitis in whom faint PAB immunoreactivity was detected in inflammatory cells. Conclusions: P. acnes was detected from granulomas formed in the epiretinal membrane of patients with sarcoidosis. The significance of P. acnes in the pathogenesis of uveitis associated with sarcoidosis remains to be determined.